Pragmatism Education Philosophy and its Implications for History Learning - Maulidan, Aldi Cahya; Saripudin, Didin; Ma'mur, Tarunasena (Universitas Negeri Semarang, 2024)
This research is motivated because during history learning less space to students because it emphasizes mastery of memorization, but in the philosophy of Pragmatism, students are given the opportunity to develop all the potential they have. This research aims to describe the philosophy of Pragmatism education in history learning. This research uses the literature study method. Literature study is a method that involves reviewing various literatures, such as books, journals, and other written sources related to the research topic. The literature study begins with determining the research topic, searching for relevant literature through various sources, analyzing each source by considering the credibility, relevance, and strength of the arguments offered. In the analysis stage, three steps are carried out, namely data reduction, data presentation, and conclusion drawing. Based on the results of the study of educational philosophy, Pragmatism was born in the 19th century, and the 20th century began to develop. Pragmatism education philosophy emphasizes the importance of practical experience and relevance in the learning process. In the context oh history learning, this approach encourages learners not only to memorize facts, but also to understand how historical events relate to their lives today. Pragmatism in history education invites learners to think critically about past events and analyze their impact on the present. This helps develop learners' ability to connect different historical periods and understand patterns of social change.